Multiple Coronary Artery Microfistulas in a Girl with Kleefstra Syndrome - Euthymia Vargiami; Athina Ververi; Hamda Al-Mutawa; Georgia Gioula; Spyridon Gerou; Fotios Rouvalis; Marios Kambouris; Dimitrios I. Zafeiriou (Case Reports in Genetics)
Kleefstra syndrome is characterized by hypotonia, developmental delay, dysmorphic features, congenital heart defects, and so forth. It is caused by 9q34.3 microdeletions or EHMT1 mutations. Herein a 20-month-old girl with Kleefstra syndrome, due to a de novo subterminal deletion, is described. She exhibits a rare and complex cardiopathy, encompassing multiple coronary artery microfistulas, VSD/ASD, and PFO.